Synthesis and structure regulation of armor-wearing biomass-based porous carbon: Suppression the leakage current and self-discharge of supercapacitors. (30th August 2022) - Li, Wei; Yang, Xiaomin; Chen, Zhimin; Lv, Ting; Wang, Xiaofeng; Qiu, Jieshan
Abstract: Biomass-based porous carbon is a very promising electrode material for supercapacitors, but adverse leakage current and self-discharge has hindered its practical applications. Herein, high-performance armor-wearing biomass-based porous carbon (NP-RHPC) was prepared with finely adjustable surface properties and micro-structure using rice husk as carbon source and coal pitch as chemical modification reagent. The synergetic effect of the stable biochar skeleton and the pitch carbon armor ensures NP-RHPC has low leakage current and self-discharge, long cyclic stability, and good rate performance. The leakage current and open circuit voltage attenuation rate of NP-RHPC are lower than those of N-RHPC without pitch carbon armor and the commercial capacitor carbon of YP-50F. The synthesized NP-RHPC has ideal specific capacitance of 209.2 F g −1 and the capacitance retention rate is up to 95.0% over 20, 000 cycles at a high current density of 1.0 A g −1, which is higher than that of N-RHPC. This impressively long-term cyclic performance of NP-RHPC can be ascribed to the excellent electrical conductivity and especially the reduction of the unstable oxygen-containing groups. This study provides insights for the rational design of high-performance armor-wearing biomass-based porous carbon electrode material towards the advanced application of biomass and coal pitch in energy storage. Graphical abstract: A high-performance armor-wearing biomass-based porous carbon electrode material was prepared with finely adjustable surface properties and micro-structure using biochar as stable skeleton and pitch carbon as armor, which can effectively suppress the leakage current and self-discharge and increase the cyclic stability and rate performance of supercapacitors. Image 1 Highlights: A high-performance armor-wearing biomass-based porous carbon electrode material (NP-RHPC) was prepared with finely adjustable surface properties and micro-structure. The synergetic effect of the stable biochar skeleton and the pitch carbon armor ensures NP-RHPC has low leakage current and self-discharge, long cyclic stability, and good rate performance. The possible suppression mechanism of self-discharge for NP-RHPC was proposed.